HUMAN PAPILLOMA VIRUS VACCINE - Bayu Mahendra, Nyoman (Medicina; Vol 43 No 2 (2012): Mei 2012, 2013)
Cervical cancer is the most common gynecologic cancer in womer, and it has the highest cancer-related deaths in developing country. The incidences kept increasing every year, associated with  delay on diagnosis, limited human resources, knowledge, education, facilities, and influence of socioeconomicculture. Currently, infection of oncogenic group high risk human papillomavirus (HPV), especially HPV-16 and HPV-18 has been widely accepted as the cause of cervical cancer. The finding of  HPV vaccine brings new hope to all of us. With primary prevention, the incidence can be brought down. Later on, every women can be freed from in cervical cancer
Keywords: human papilloma virus, vaccine